Femoral Nerve Block Relieves Preoperative Pain in Elderly Patients with Femoral Neck Fracture - Jing ZHANG; Xuejian ZHANG; Tingting WANG; Shanshan NIE; Xuyue PAN; Yue TANG; Ling TANG (国际转化医学杂志（英文版）, 2019)
Objective: To investigate the effectiveness and clinical value of preoperative femoral nerve block in relieving pain of femoral neck fracture in the elderly patients. Methods: A total of 186 patients who underwent surgical treatment for femoral neck fractures in our hospital from January 2012 to December 2016 were randomly divided into intervention group (treated with femoral nerve block, 95 cases) and control group (treated with oral opioid drugs, 91 cases), and the visual analogue scale (VAS) was used to assess the degree of pain relief at each time point after treatment. Results: A total of 186 patients were enrolled in the study, with an average age of (78.31 ± 6.44) years, of which 54.84％ were women. Compared with the control group, the VAS score of the intervention group was significantly lower than that of the control group at the 12th hour after treatment, and the two groups were statistically significant (P < 0.05). The VAS score of the intervention group decreased from baseline to 12 hours after surgery. The value was also significantly higher than that of the control group (P < 0.05). The opioid analgesic dose in the intervention group was significantly lower than that in the control group, and the two groups were statistically significant [(2.3 ± 4.0) mg vs. (5.7 ± 5.2) mg, P < 0.001]. Conclusion: Preoperative femoral nerve block can relieve pain of elderly patients with femoral neck fracture and reduce the dose of opioids. Femoral nerve block may be a feasible analgesia for patients with femoral neck fracture in the elderly patients.